Accessibility as a means to realising social justice in higher education: Interviews with user organisations and service-providers - Hermosa-Ramírez, Irene; Arias-Badia, Blanca (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
Media Accessibility research – “concerning access to media and non-media objects, services and environments through media solutions, for any person who cannot or would not be able to [...] access them in their original form” (Greco, 2019, p. 18) – has thus far focused mostly on aspects related to cultural life. However, access services such as subtitles, sign language interpreting and web accessibility are also deployed in higher education, a context where people with sensory disabilities are still underrepresented. The present article aims to assess accessibility needs and current barriers in the context of higher education in Spain. To gain a better understanding of access provision in universities and following a user-centred approach, the article reports on the results of semi-structured interviews with five disabled people organisations and two accessibility professionals. The thematic analysis of the interviews reveals several areas of concern: a generalised need for accessibility literacy, both required at a societal level and at an individual level (especially on the part of university staff), a prevalence of invisible work among students with disabilities who have to take extra steps to have their accessibility needs met, and the improvable working conditions of accessibility professionals providing services in the context of higher education.